Factors Influencing Patient Satisfaction in Inpatient Department of a Private Hospital in South Sumatra - Maria Ivena Kristi; Oscar Jayanagara (Green Publisher Indonesia, 2025)
study investigates the factors influencing patient satisfaction in the inpatient department of a private hospital in South Sumatra. Focusing on three key variables (nursing ratios, burnout, and interpersonal communication skills) this research explores their direct and mediated effects on patient satisfaction, with service quality serving as a mediating variable. The study employs a quantitative research method, utilizing a cross-sectional survey design. Data were collected from nurses working in the inpatient ward, with statistical analyses performed to identify relationships between the variables. The findings reveal significant correlations: higher nursing ratios and burnout negatively impact service quality and patient satisfaction, while effective interpersonal communication skills positively influence these outcomes. Service quality is shown to mediate the relationship between the independent variables and patient satisfaction, underscoring its critical role in healthcare delivery. These results provide actionable insights for hospital administrators, emphasizing the need to optimize staffing levels, address nurse burnout, and enhance communication skills to improve patient satisfaction. This research contributes to the academic understanding of patient satisfaction determinants in the context of Indonesian private healthcare and offers practical implications for improving hospital management and patient care strategies. The study highlights the importance of tailored interventions to address the unique challenges faced by private hospitals in South Sumatra.